Effects of niacin on atherosclerosis and vascular function. - Ruparelia, N; Digby, J; Choudhury, R (2011)
PURPOSE OF REVIEW: Niacin has been used for more than 50 years in the management of atherosclerosis and is associated with improved patient outcomes. The routine use of niacin has been superseded in recent years with the advent of newer lipid-modulating interventions. Recently, however, there has been a renewed interest in its use due to the appreciation of its many beneficial effects on atherosclerosis and endothelial function, both 'lipid-targeted' and 'pleiotropic'. This review will consider the effects of niacin in the setting of clinical trials and will critically evaluate proposed mechanisms of action. RECENT FINDINGS: The identification of the GPR109A receptor has promoted a greater insight into niacin's mechanism of action, with demonstrated beneficial effects on endothelial function and inflammation, in addition to its lipid modulation role. SUMMARY: Whether niacin itself is used routinely in the future will depend on the outcomes of two large outcome trials (AIM-HIGH and HPS2-THRIVE). In the future, however, with even better understanding of niacin pharmacology, new drugs may be able to be engineered to capture aspects of niacin that capitalize on the benefits more specifically and also more selectively, to avoid troublesome side-effects.